Pollination of invasive Rhododendron ponticum (Ericaceae) in Ireland - STOUT, JANE CATHERINE (EDP Sciences, 2007)
Several insect species visited exotic Rhododendron ponticum flowers, but bumblebees were most common. Only bumblebees (and one Vespula) contacted the flower stigma whilst foraging and are probably the main pollinators. One-third of insect visits resulted in stigma contact and visitation rates were high. This explains the high seed set reported elsewhere. There were significant differences according to the body size of visitors, with large queen bees contacting stigmas more often than smaller workers. There were no significant differences in behaviour of three species (Bombus jonellus, B. lucorum and B. monticola) and all bees tended to move short distances between flowers on a single plant. Longer flights and movements among plants were rare. Pollen carryover was estimated to be high: there was no decline in the amount of pollen deposited on stigmas from the first to fifth flower visited. The impact of bee behaviour on reproduction and invasion by exotic R. ponticum is discussed.
null
Keywords: body size; exotic plant; invasion; pollen transfer; weeds; pollination; insect